The Influence of Profitability, Intellectual Capital, and Investment Decisions on Company Value with Company Size as a Moderating Variable - Yuyun Yunaningsih; Susanti Widhiastuti (GoodWill, 2025)
This study investigates the influence of profitability, intellectual capital, and investment decisions on firm value, with firm size as a moderating variable, in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) via WarpPLS 8.0, the study analyzes secondary data from 45 firms. The results indicate that profitability and intellectual capital have a significant positive effect on firm value. In contrast, investment decisions exhibit a negative but statistically insignificant effect. Furthermore, firm size significantly moderates the relationship between the three independent variables and firm value, strengthening the influence of profitability, intellectual capital, and investment decisions. These findings support the signaling theory and resource-based theory, emphasizing the strategic importance of profitability and intangible assets in enhancing firm value. The study contributes to the literature by providing empirical evidence on the role of firm size as a moderator in the Indonesian property sector. Recommendations are proposed for managerial decision-making, particularly in optimizing profitability, intellectual capital management, and investment strategies.